Haemoptysis as the sole presenting symptom of dissection of the aorta. - Guidetti, A S (1989)
A 75 year old man who had had haemoptysis for 24 hours was found to have his left lower lobe compressed by a dissection of the aorta, which was otherwise symptomless.